Composition and abundance of cockroaches in traditional markets of Purwokerto City, Indonesia - TRISNOWATI BUDI AMBARNINGRUM; IMAM WIDHIONO; ENDANG SRIMURNI KUSMINTARSIH; HERY PRATIKNYO; TRISNO HARYANTO; FATHIMAH NURFITHRI HASYIFAH (Society for Indonesian Biodiversity, 2024)
Abstract. Ambarningrum TB, Widhiono I, Kusmintarsih ES, Pratiknyo H, Haryanto T, Hasyifah FN. 2024. Composition and abundance of cockroaches in traditional markets of Purwokerto City, Indonesia. Biodiversitas 25: 2773-2779. Markets with high human activity and abundant food are ideal conditions for cockroaches. This study aimed to investigate the composition and abundance of cockroaches infesting three markets in Purwokerto City, Central Java, Indonesia. To achieve this objective a survey method with random sampling used baiting traps and hand collection. The analysis used the Shannon-Wiener index (H'), Evenness index, relative abundance, and density index. The results showed that three cockroach families were identified, namely Blattellidae, Blattidae, and Blaberidae. The cockroaches found in markets 1 and 3 consisted of five species, namely Blattella germanica (Linnaeus, 1767), Periplaneta americana (Linnaeus, 1758), Blatta lateralis (Serville, 1838), Nauphoeta cinerea (Olivier, 1789), and Pycnoscelus surinamensis (Linnaeus, 1758), while in Market 2 there were only three species, namely B. germanica, P. americana, and N. cinerea. The total population were 2467, 81, and 3627 individuals in Market 1, 2, and 3 respectively. The B. germanica predominated in Markets 1 and 2, while N. cinerea dominated in Market 3. Furthermore, density levels varied across markets, showing differing infestation intensities. The study explained the importance of integrated pest management strategies and regular monitoring to control cockroaches population effectively. These results provide valuable insights for local pest control efforts aimed at maintaining hygiene and health standards in market environments.